Designing Supertough and Ultrastretchable Liquid Metal-Embedded Natural Rubber Composites for Soft-Matter Engineering - Banerjee, Shib Shankar; Mandal, Subhradeep; Arief, Injamamul; Layek, Rama Kanta; Ghosh, Anik Kumar; Yang, Ke; Kumar, Jayant; Formanek, Petr; Fery, Andreas; Heinrich, Gert; Das, Amit (ACS Applied Materials and Interfaces, 2021)
Functional elastomers with incredible toughness and stretchability are indispensable for applications in soft robotics and wearable electronics. Furthermore, coupled with excellent electrical and thermal properties, these materials are at the forefront of recent efforts toward widespread use in cutting-edge electronics and devices. Herein, we introduce a highly deformable eutectic-GaIn liquid metal alloy-embedded natural rubber (NR) architecture employing, for the first time, industrially viable solid-state mixing and vulcanization. Standard methods of rubber processing and vulcanization allow us to fragment and disperse liquid metals into submicron-sized droplets in cross-linked NR without compromising the elastic properties of the base matrix. In addition to substantial boosts in mechanical (strain at failure of up to μ650%) and elastic (negligible hysteresis loss) performances, the tearing energy of the composite was enhanced up to 6 times, and a fourfold reduction in the crack growth rate was achieved over a control vulcanizate. Moreover, we demonstrate improved thermal conductivity and dielectric properties for the resulting composites. Therefore, this work provides a facile and scalable pathway to develop liquid metal-embedded soft elastomeric composites that could be instrumental toward potential applications in soft-matter engineering.
CRIS-Team Scopus Importer:2022-04-14
Keywords: fracture toughness; liquid metal fillers; soft rubber composites; tearing energy